Pharmacological activities and benefits of coconut water in plant tissue culture: a review / Nur Dayana Athirah Kamaruzzaman, Norrizah Jaafar Sidik and Azani Saleh - Kamaruzzaman, Nur Dayana Athirah; Jaafar Sidik, Norrizah; Saleh, Azani (2018)
Cocos nucifera (L.) belongs to Arecaceae family is a type of highly valuable plant species due to its medicinal values. It is a widespread fruit at the area of Southeast Asia and commonly known as “coconut tree”. The fruit part of Cocos nucifera (L.) contains coconut water that have many pharmacological activities which can give benefits for human health and also give benefits for plant in tissue culture Therefore, coconut water has been associated very well in various tribes around the world with diverse biological effects for human such as anti-inflammatory, antifungal, antioxidant, renal protective and cardio protective activity. Besides that, coconut water was noted for its wide application in plant tissue culture due to its nutrients content. It was reported to be served as the organic additives for plant to enhance callus induction and proliferation, shoot and root elongation/regeneration and somatic embryogenesis in tissue culture. The present article will discuss the pharmacological activities of coconut water as well as its benefits for plant in tissue culture which had been proven based on recent scientific research.